Análisis de la Inversión Extranjera, por sectores de actividad económica en el Ecuador, durante el periodo 2010 -2016 - Rodríguez Real, Enrique Orlando (2018)
Foreign investment is the direct or indirect way to invest in a region, through several ways related to the economy, in order that the economic capital of a state grows, taking into account that this capital comes from foreign funds, towards a civil person, national companies of productive character, or directly with entities belonging to the governmental system, in such a way that these are in charge of the administration of the productive sectors of the country. This investigation perceives a development of several cycles that start from the bibliographic compilation of the topics to be treated during the periods to be investigated, up to the total analysis of what this activity has entailed, this is how this investigative study will be related to statistical tables that show how much foreign investment has been, as has been its durability, what have been the qualities, advantages and disadvantages that have been promoted during the permanence of this economic activity. Through the present investigation carried out on foreign direct investment, intends to make an analysis of how this economic activity influences the sectors of economic activity in Ecuador, which are the main sectors benefited, as has been the emergence of this economic activity within of the periods of analysis; if the permanence of this activity has led to progress in the country's economic growth; among other study parameters established within the investigation. The main objective of the research is to analyze how foreign direct investment occurs by sectors of economic activity within the periods 2010-2016; in such a way that this objective will always be taken into account as a starting point within the investigation of bibliographic sources, becoming the main axis for the development of research. The methodology implemented is going to be non-experimental because the variables are not going to be manipulated, what is going to be done is a description of the phenomenon that is being investigated. It should be noted that several essential steps coexist, such as the observation of the phenomenon and the existence of a problem to explain this phenomenon.